USULAN MANAJEMEN RISIKO DAN MATRIKS KEY RISK INDICATOR PADA SISTEM RANTAI PASOK DI PT MEPROFARM - Dio Anugrahtama, Dionisius
PT Meprofarm is a company engaged in the production of medicines. As a manufacturing company, PT Meprofarm also carries out supply chain functions. But, there are still problems with the supply chain, as in 2019 there were 143 transactions with late order fulfillment. The problem is triggered by the various risks that occur in the supply chain systems, so this research will try to make a risk management proposal. In addition, a key risk indikator matrix will be created to assist PT Meprofarm in monitoring identified risks. The framework used is a risk management framework according to the Project Management Institute and the creation of KRI matrix according to COSO. Research begins with a risk planning process related to the scope and methods of risk management. Next, identify all possible risks that will occur. Then a risk analysis is carried out, which assesses the risk level into five values, namely very low, low, medium, high, and extreme. Then the risk response planning is carried out for high-value risks. Last is risk control and monitoring. To facilitate the risk monitoring process, a key risk indicator (KRI) is used, which provide an initial signal if there is a change in risk exposure. The results showed there are 64 risks recorded at PT Meprofarm. Of the 64 risks, there are 4 very low-value risks, 30 low-value risks, 26 medium-value risks, and 4 high-value risks. Then do the planning of risk responses to 4 high-value risks. The final step is risk control and monitoring. The KRI matrix is made, which contains indicators and value thresholds, to facilitate company to monitor and control these 4 high-value risks.